Clinical features of post-radiation nasopharyngeal necrosis and their outcomes following surgical intervention in nasopharyngeal cancer patients. (March 2021) - Yang, Kyungmi; Ahn, Yong Chan; Nam, Heerim; Hong, Sang Duk; Oh, Dongryul; Noh, Jae Myoung
Highlights: PRNN was rare, but more frequently occurred after re-RT group and in older ages. PRNN occurred with similar time-course after re-RT and single RT. Endoscopic debridement with nasoseptal flap was effective to resolution of PRNN. Multidisciplinary management is needed for timely and appropriate care of PRNN. Abstract: Purpose: To investigate the incidence and clinical features of post-radiation nasopharyngeal necrosis (PRNN), and effectiveness of surgical intervention for its treatment. Materials and Methods: Retrospectively, we reviewed 380 NPC patients who underwent high dose radiotherapy (RT) (single RT in 355 and re-RT in 25) from January 2008 till December 2017 at the authors' institute, among who 22 developed Grade ≥ 3 PRNN. The management of PRNN was discussed through weekly multidisciplinary head and neck oncology conference, and surgical debridement was performed when feasible. Results: The incidence of PRNN was significantly higher following re-RT than in single RT (11/355, 3.1% vs. 11/25, 44.0%, p  < 0.001). The PRNN patients in single RT group tended to be older and had more advanced initial tumor extents. The intervals from the latest RT start till PRNN assignment were similar between groups (7.3 vs. 6.6 months, p  = 0.140). Nineteen patients underwent surgical debridement: two open; and 17 endoscopic approach, respectively. Endoscopic mucosal reconstruction was performed in eight patients. Resolution of PRNN was achieved in 11 patients (64.7%). The rates of 3-year overall survivals (OS) from the initial RT, latest RT (adjusting re-RT), and PRNN assignment were 84.4%, 70.9%, and 54.7%, respectively. Eight patients (36.4%) succumbed to death: NPC progression in three (13.6%); evidently PRNN-related events in two (9.1%), probably PRNN-related events in two (9.1%); and inter-current death in one (4.5%), respectively. Conclusion: PRNN needs close collaboration among head and neck oncologists and could be successfully recovered, without compromising survival, following timely surgical intervention.